COMPARATIVE STUDY ON TRANSSEPTAL APPROACH VS TRANS LEFT ATRIAL APPROACH FOR MITRAL VALVE PROCEDURE. - Sangram Keshari Behera; Soumyadipta Mishra; Deepak Narayan Sahoo; Latika Kalra (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Objective: This study aims to compare the two approaches of mitral valve exposure in isolated mitral valve disease for their intra-operative and post-operative outcomes. Material and Methods: All patients who underwent isolated mitral valve surgery from May 2022 to March 2023 were enrolled in the study, after they met the inclusion and exclusion criteria. Patients include only mitral valve disease. Patient with severe LV dysfunctions and patient with bleeding tendency were excluded. We had taken into account are operating time, post op bleeding and arrythmia. Results: After analysing total pump time, total aortic cross clamp time, post operative bleeding and arrythmia in both the group, there was no significantdifferences in outcome in any of the methods. Conclusion: The LA approach is the most used approach which provides satisfactory exposure of the mitral valve and the sub valvar apparatus. However, patient characteristics and circumstances limit the versatility of this approach.The TS approach provides optimal exposure of the mitral valve complex even in the presence of inexperience assistant surgeons or trainee surgeons or hostile anatomical conditions or redo surgeries. Studies have associated the transseptal approach with multiple complications of excessive bleeding, post operative rhythm disturbances and subsequent need for pacemaker implantation. After comparison of multiple intra-operative and post-operative variables, we found that the TS approach is a valuable approach to the mitral valve providing excellent visibility even in hostile anatomy or operative conditions delivering comparable results to the conventional LA approach.